2005
DOI: 10.1158/1078-0432.ccr-05-0249
|View full text |Cite
|
Sign up to set email alerts
|

2-[18F]Fluoro-2-Deoxyglucose Positron Emission Tomography for the Detection of Disease in Patients with Prostate-Specific Antigen Relapse after Radical Prostatectomy

Abstract: Experimental Design: Retrospective cohort study in 91patients with prostate-specific antigen (PSA) relapse following prostatectomy, imaged with 2-[18 F]fluoro-2-deoxyglucose positron emission tomography (FDG-PET) in a tertiary care cancer center between February 1997 and March 2003. Comparison was made with magnetic resonance imaging (n = 64), bone scan (n = 56), and computed tomography (n = 37). The standard of reference included biopsy or clinical and imaging follow-up. We calculated sensitivity and specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
88
0
11

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 190 publications
(102 citation statements)
references
References 40 publications
(28 reference statements)
3
88
0
11
Order By: Relevance
“…18 F-FDG is the most widely used radiotracer in oncologic PET/CT imaging; however, only a minority of PC (i.e., only aggressive, poorly differentiated, or undifferentiated PC) shows a high glycolytic rate, limiting the use of 18 F-FDG PET (7,8). In Europe, radiolabeled choline derivatives ( 18 F-fluorocholine or 11 C-choline) were among the most commonly used PET tracers for PC imaging.…”
mentioning
confidence: 99%
“…18 F-FDG is the most widely used radiotracer in oncologic PET/CT imaging; however, only a minority of PC (i.e., only aggressive, poorly differentiated, or undifferentiated PC) shows a high glycolytic rate, limiting the use of 18 F-FDG PET (7,8). In Europe, radiolabeled choline derivatives ( 18 F-fluorocholine or 11 C-choline) were among the most commonly used PET tracers for PC imaging.…”
mentioning
confidence: 99%
“…Schö der et al 23 showed that the proportion of FDG-PET-positive studies was significantly higher in patients with post-prostatectomy biochemical recurrence with higher PSA values. Although low PSA did not necessarily preclude PET positivity, 18 F-FDG-PET was most useful with PSA 42.4 ng ml À1 or a PSA velocity 41.3 ng per ml per year.…”
Section: Impact Of Psa Level On Pet Imaging Findingsmentioning
confidence: 99%
“…Thus, rather than simply replacing a tracer with another, a multitracer approach may be needed to fully exploit the potential of PET imaging in the setting of biochemical failure. 23,56 …”
Section: Choice Of Pet Tracermentioning
confidence: 99%
See 2 more Smart Citations